Optimalisasi Pembelajaran IPA melalui Inkuiri Terbimbing dengan Google Lens untuk Meningkatkan Hasil Belajar Siswa Kelas VII SMP PGRI Poopo - Dani Lii; Masje Wurarah; Aser Yalindua (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
The issue faced in current learning is that it is still teacher-centered, which leads to low student interest and motivation in learning. Additionally, students' attention during lessons is lacking, and they tend to get bored, resulting in poor learning outcomes. This study aims to examine the application of the Guided Inquiry learning model assisted by the Google Lens application to improve the science learning outcomes of seventh-grade students at SMP PGRI POOPO. The subjects of this study were 39 seventh-grade students in the second semester of the 2023/2024 academic year. This research utilized a classroom action research method in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results of the study showed a significant improvement in student learning achievement. The classical completeness percentage in Cycle I was 52.63%, while in Cycle II, it increased to 84.21%. Based on these findings, it can be concluded that implementing the Guided Inquiry learning model supported by the Google Lens application can improve science learning outcomes for seventh-grade students at SMP PGRI POOPO. This model is expected to make students more active, interested, and motivated in learning, leading to better learning outcomes.